Effects of exogenous calcium additions on the ecological stoichiometric characteristics of various organs and soil nutrients and their internal stability in Pinus tabuliformis - Li, Hui; Zhao, Yaoyao; Weng, Xiaohang; Zhou, Yongbin; Huo, Yan; Zhang, Songzhu; Liu, Liying; Pei, Jiubo (Frontiers in Plant Science, 2024)
Introduction Pinus tabuliformis as a crucial afforestation species in semi-arid regions, faces issues such as the reduction of plantations. Calcium plays a significant role in alleviating drought stress and promoting nutrient uptake in plants. Methods Utilizing a pot experiment approach, seedlings were treated with exogenous calcium at five concentrations (0, 50, 100, 200, and 400 mg•kg-1). The nutrient content of the plants and soil was measured, and their ecological stoichiometric characteristics and internal stability were analyzed. This was followed by a series of related studies. Results As the concentration of calcium increases, the contents of carbon, nitrogen, phosphorus, and potassium in various organs and the whole plant exhibit a trend of first increasing and then decreasing, peaking at calcium treatment of 50-100 mg•kg-1. Concurrently, the calcium concentration in plant organs and the entire plant gradually increases with the availability of calcium in the soil. The addition of exogenous calcium has a certain impact on the ecological stoichiometric ratios (C:N, C:P, N:P) of Pinus tabuliformis seedlings' leaves, stems, roots, and the whole plant, exhibiting distinct variation characteristics. At calcium concentrations of 50-100 mg•kg-1, the ratios of C:N and C:P are relatively lower. Under calcium concentrations of 0, 50, and 100 mg•kg-1, soil calcium shows a positive correlation with the total carbon (TC), total nitrogen (TN), total phosphorus (TP), total potassium (TK), and calcium contents in leaves, stems, roots, and the entire plant. However, at calcium concentrations of 200 and 400 mg•kg-1, soil calcium exhibits a significant positive correlation with the calcium content in leaves, stems, roots, and the entire plant, and a significant negative correlation with the total phosphorus, total nitrogen, total phosphorus, and total potassium contents. After the addition of exogenous calcium at different concentrations, most stoichiometric indices of various organs of Pinus tabuliformis seedlings demonstrate strong balance. Discussion Calcium, as an essential structural component and second messenger, regulates the nutrient uptake and utilization in plants, influencing the stoichiometry. However, both low and high concentrations of calcium can be detrimental to plant growth by disrupting nutrient metabolism and internal structures. Consequently, there exists an optimal calcium concentration for nutrient absorption.